2003
DOI: 10.1093/nar/gkg464
|View full text |Cite
|
Sign up to set email alerts
|

Human activation-induced cytidine deaminase causes transcription-dependent, strand-biased C to U deaminations

Abstract: Activation-induced cytidine deaminase (AID) is required for the maturation of antibodies in higher vertebrates, where it promotes somatic hypermutation (SHM), class switch recombination and gene conversion. While it is known that SHM requires high levels of transcription of the target genes, it is unclear whether this is because AID targets transcribed genes. We show here that the human AID promotes C to T mutations in Escherichia coli which are stimulated by transcription. The mutations are strand-biased and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
227
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(244 citation statements)
references
References 28 publications
14
227
3
Order By: Relevance
“…In the E. coli studies, a specific increase in C3T mutations has been attributed to enhanced deamination of cytosines located on the NTS, presumably because of the transcription-associated single-stranded character of this strand (3). It has recently been demonstrated that cytosines on the NTS are preferred targets for AID, a deaminase involved in initiating somatic hypermutation of immunoglobulin genes (35,37). In addition to enhancing BS, an increase in large deletions that inactivate a plasmid-based lacZ target has been reported when high levels of transcription oppose the direction of replication fork movement in E. coli (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the E. coli studies, a specific increase in C3T mutations has been attributed to enhanced deamination of cytosines located on the NTS, presumably because of the transcription-associated single-stranded character of this strand (3). It has recently been demonstrated that cytosines on the NTS are preferred targets for AID, a deaminase involved in initiating somatic hypermutation of immunoglobulin genes (35,37). In addition to enhancing BS, an increase in large deletions that inactivate a plasmid-based lacZ target has been reported when high levels of transcription oppose the direction of replication fork movement in E. coli (40).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription bubbles, structures in which ssDNA is exposed due to helicase activity of the RNA polymerase complex, are known targets of AID [65][66][67][68] and represent a likely source of mutations in coding regions if replication occurs before repair of dU.…”
Section: Availability Of Ssdna Substratementioning
confidence: 99%
“…So, the appearance of a class-switch reaction was dependent on the evolution of switch-region sequences. AID-like and uracil-DNA glycosylase (UNG)-like proteins, which are involved in these processes, had ancient origins, co-evolving with innate immune antiviral defences [49][50][51] .…”
Section: Transitions From Innate To Adaptive Immunitymentioning
confidence: 99%
“…So, the appearance of a class-switch reaction was dependent on the evolution of switch-region sequences. AID-like and uracil-DNA glycosylase (UNG)-like proteins, which are involved in these processes, had ancient origins, co-evolving with innate immune antiviral defences [49][50][51] .Over time, V-gene duplication and germline substitutions, which were focused in COMPLEMENTARITY-DETERMINING REGION 1 (CDR1) and CDR2, coupled with combinatorial joining, imparted a considerable selective advantage in terms of deriving receptor diversity. Somatic hypermutation of immunoglobulin genes, which is a central feature of BCR maturation, occurs in the earliest extant jawed vertebrates -the cartilaginous fish 52,53 -and might be an accentuation of a genome-wide process 54,55 .…”
mentioning
confidence: 99%